Pemberdayaan Masyarakat Desa Dalam Mengembangkan Pariwisata dan Ekonomi Kreatif di Desa Wisata Cemagi Kabupaten Badung - Ni Nyoman Arini; Mekarini, Ni Wayan; Wartana, I Made Hedy; Clarissa, Sarita Vania; Sunata, I Made (Sevanam: Jurnal Pengabdian Masyarakat, 2024)
Community Service Activities (PkM) through KKN activities in Cemagi Village in 2023 are further KKN activities, based on Memorandum of Understanding (MoU) between Triatma Mulya University and Cemagi Village for 3 years, so that this Thematic KKN activity can be carried out sustainably in Cemagi Village. KKN activities of the Faculty of Business and Tourism, Triatma Mulya University were held for 5 (five) weeks in Cemagi Tourism Village which took place from January 16 to February 17, 2023. This service article analyzes the empowerment of village communities in developing tourism and the creative economy in Cemagi Tourism Village, Badung Regency. This research began with the 2023 Thematic Real Work Lecture (KKN) activities held in Cemagi Village. The implementation of KKN activities is carried out through several stages, namely the planning, implementation, monitoring and evaluation stages. The Thematic KKN Team of the Faculty of Business and Tourism, Triatma Mulya University provided socialization related to tourism awareness and financial literacy education. The details of the KKN work program that have been implemented in Cemagi Village are clean-up actions at Mengening Beach, cooking classes, promotional videos, financial literacy education, making and installing welcome billboards in Cemagi Village, teaching English and basic mathematics to kindergarten children, socializing waste sorting, and quiz competitions. A pre-planned work program can be completed in a timely manner.